RESPONS PERTUMBUHAN DAN PRODUKSI KEDELAI TERHADAP PEMBERIAN MIKORIZA DAN PENGGUNAAN UKURAN BIJI PADA TANAH SALIN - Andriany F Damanik; Rosmayati Rosmayati; Hasmawi Hasyim (Jurnal Agroekoteknologi, 2013)
Respons on growth and yield of soybean by giving mycorrhiza and use of seeds size in saline soil.  Grobogan variety has advantages advantages flourescent, large pods and pod maturity simultaneously. Mycorrhiza is an association between certain fungi with the roots of the plant by forming a complex tangle of interactions. Saline soil is soil containing soluble salts are large enough for the growth of most plants such as hydrochloric or sulfuric. The aim of this research was to know response on growth and yield of soybean by giving mycorrhiza and use of seeds size in saline soil. Research conducted at the field experiment of Tanjung Rejo village Percut Sei Tuan, Deli Serdang on March-August 2012, using a randomized block design factorial with two factors and six replications. The first factor was grobogan variety seeds size, large seeds (13-17 g/100 seeds) and small seeds (8-11g/100 seeds). The second factor was Mycorrhiza (0 and 10 g/plant). The results showed that seed size were significantly different to plant height, number of branches, flower initiation, degree of infection, harvesting age, number of  fill pods per plant and seed production per plant. Mycorrhiza were significantly different to number of branches, degree of infection. Interaction between the seeds size and mycorrhiza did not give significant effect for all parameters.   Keywords: soybean, mycorrhiza, saline soil